Advanced memristive architectures based on nanomaterials for biomedical applications: a mini review - Bouzouita, Manel; Pathak, Shashikant; Zayer, Fakhreddine; Belgacem, Hamdi; Tzouvadaki, Ioulia (Frontiers in Nanotechnology, 2025)
In recent years, the interest of science in big data sensing, storage and processing has been growing fast. Nano-materials have been widely used in resistive switching devices thanks to their distinguished properties. Furthermore, they provide nano-scale dimensions and compatibility with fabrication procedures and complementary metal oxide semiconductor (CMOS) technology. Nano-materials can also enhance the performance of memristive structures. The operation of a memristor, which enables efficient resistive switching characterized by fast response, increased storage density, and low power requirements, depends largely on nano-materials and deposition techniques. Herein, a comprehensive brief review of nano-material RRAM arrays and their application in biomedical is discussed. First, we introduce planar and array resistive switching structures. Second, we report the different nanomaterial categories that can be used in resistive random-access memories (RRAMs). Then, we focus on the integration of 3D nano-material-based memristive crossbars for in-memory computing and biosensing arrays and discuss representative applications. The exploration of nano-materials enables the development of enhanced resistive switching architectures with increased signal integrity, great speed, and ultra-high sensitivity towards thermally and electrically stable memristive biomedical platforms.